Application of Cutinase in Papermaking Industry - Zheng Fei Yan (Cutinase: Preparation and Application, 2021)
Recycling of waste paper can solve problems of resource and energy shortages, which was considered as an effective and low-cost method. So far, deinking and adhesive removal have become the key factor in the recovery and utilization of waste paper. Enzymatic treatment is less polluting and eco-friendly, which has drawn extensive attention. This study provides a potential strategy for biodeinking by using cutinase. The brightness of the deinked papers realized 42.01% for 8 U/g T. fusca cutinase at pH 8 and 60\(^°\)C for 30 min; 41.62% for 8 U/g F. solani pisi cutinase at pH 8.5 and 35\(^°\)C for 30 min. These brightness values are higher than that for chemical deinking by 5.13 and 4.38%, respectively. During the recycling of waste paper, the accumulation of polyacrylates could decrease the quality of the recycled paper and increase the usage of circulating water by the formation of tacky substances known as stickies. Cutinases have the hydrolytic capacity for polyacrylates, which can minimize or eliminate the deposition of stickies. T. fusca cutinase favored the hydrolysis of PEA over PMA dispersions at 0.5 mg/mL, which could limit the turbidity decrease to about 1.0%. Meanwhile, the optimal dosage of T. fusca cutinase was lower than those of F. solani pisi and Humicola insolens cutinases.